Spatial accessibility of bicycle routes in the Quad Cities: impacts for environmental justice. Issue 3 (3rd July 2021) - Parker, Sadie K.; Hinson, Haily M.; Porter, Rob
ABSTRACT: This study uses an environmental justice framework to analyze the population along the Quad Cities' bikeway network. The sociodemographic profiles of census block groups within 400 metres of a bike route are compared to those outside of 400 metres in order to discern if there is equitable distribution. Using binary logistic regression, four sociodemographic variables – lower-income, minority, short-term residency, and college-educated – were found to significantly increase a census block group's odds of being within 400 metres of a bike route. Our results suggest little to no environmental injustices are occurring in regard to the spatial accessibility of bike routes in the Quad Cities area, though they may indicate the start of gentrification within these neighbourhoods. The study discusses that the placement of bike routes was not a purposeful act of environmental justice and that to maintain such a status community leaders will need to make a conscious commitment to environmental justice.